Outcomes of Scleral Buckle Removal: Experience from the Last Decade. (4th May 2017) - Moisseiev, Elad; Fogel, Miri; Fabian, Ido Didi; Barak, Adiel; Moisseiev, Joseph; Alhalel, Amir
ABSTRACT: Purpose : To evaluate the indications, outcomes, and complications of scleral buckle removal over the past decade and compare to previously published data. Methods : Forty nine eyes of 49 patients who underwent scleral buckle removal and had at least 6 months of follow-up were included in this retrospective study. Recorded parameters included demographic information, history of the retinal detachment, details of the scleral buckling surgery, indication for scleral buckle removal, time from scleral buckle placement to removal, culture results, length of follow up, visual acuity (VA) throughout the follow up, and the occurrence of any complications or need for additional surgery after scleral buckle removal. Results : The overall rate of scleral buckle removal over the last decade was 5.7% (85/1493). Indications included buckle extrusion (57.1%), infection (8.2%), both (26.5%) eyes, and strabismus and diplopia (8.2%). The median time from scleral buckle placement to removal was 35 months, but in 22.4% of cases the buckles were removed after less than 6 months, and in an additional 22.4% of cases after more than 10 years. The rate of recurrent retinal detachment after scleral buckle removal was 8.2%, with half of the cases occurring within 3 months of the removal. Conclusions : Removal of scleral buckles is associated with a 8.2% risk for redetachment. Redetachment can occur many years following the removal and long-term follow up in these patients is warranted.